2012
DOI: 10.1638/2012-0045r.1
|View full text |Cite
|
Sign up to set email alerts
|

PRESHIPMENT TESTING SUCCESS: RESOLUTION OF A NASAL SINUS GRANULOMA IN A CAPTIVE KOALA (PHASCOLARCTOS CINEREUS) CAUSED BYCRYPTOCOCCUS GATTII

Abstract: A 3-yr-old female koala (Phascolarctos cinereus) was diagnosed with a nasal sinus granuloma caused by Cryptococcus gattii after a pre-shipment examination revealed a latex cryptococcal agglutination titer of 1:512. Successful medical and surgical treatment of the granuloma was monitored using serial latex cryptococcal agglutination titers, serum levels of antifungal drugs, and advanced imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…As fluconazole displays linear pharmacokinetics (Louie et al ., ,b), it is unlikely that the dose of 25 mg/kg p.o. reported previously (Wynne et al ., ) would reach the f AUC/MIC target of 192 in any koalas, although the lower target of 12 may be attainable in some koalas. It should be noted that these targets are not definitive and can only be used as a guide to therapy, as antifungal susceptibility results are known to vary widely between laboratories and strains of C. gattii (Rex et al ., , ; Gomez‐Lopez et al ., ).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…As fluconazole displays linear pharmacokinetics (Louie et al ., ,b), it is unlikely that the dose of 25 mg/kg p.o. reported previously (Wynne et al ., ) would reach the f AUC/MIC target of 192 in any koalas, although the lower target of 12 may be attainable in some koalas. It should be noted that these targets are not definitive and can only be used as a guide to therapy, as antifungal susceptibility results are known to vary widely between laboratories and strains of C. gattii (Rex et al ., , ; Gomez‐Lopez et al ., ).…”
Section: Discussionmentioning
confidence: 96%
“…Fluconazole is an antifungal drug currently administered orally to treat cryptococcosis in koalas (Wynne et al, 2012), although pharmacokinetic parameters have not been established in this species. Previous studies in koalas have demonstrated low plasma concentrations of both the fluoroquinolone antibacterial, enrofloxacin (Griffith et al, 2010), and the nonsteroidal anti-inflammatory drug, meloxicam (Kimble et al, 2013) following oral administration of conventional doses.…”
Section: Introductionmentioning
confidence: 99%
“…The pathogen responsible for cryptococcosis in koalas is Cryptococcus gattii, which is considered part of the Cryptococcus neoformans species complex (Chen, Meyer, & Sorrell, 2014). Medicines that have been used for the systemic treatment of cryptococcosis in koalas include fluconazole (FLC) (Govendir et al, 2016;Kido et al, 2012;Woods & Blyde, 1997;Wynne et al, 2012), itraconazole (ITC) (Kido et al, 2012;Woods & Blyde, 1997;Wynne et al, 2012), and ketoconazole (Woods & Blyde, 1997). A treatment protocol of daily FLC administration with additional administration of amphotericin has also been reported (Govendir et al, 2016;Kido et al, 2012;Woods & Blyde, 1997;Wynne et al, 2012).…”
Section: Antifungalsmentioning
confidence: 99%
“…Medicines that have been used for the systemic treatment of clinical cryptococcosis in koalas include fluconazole (Govendir et al., ; Kido et al., ; Woods & Blyde, ; Wynne et al., ), itraconazole (Kido et al., ; Woods & Blyde, ; Wynne et al., ) and ketoconazole (Woods & Blyde, ). A treatment protocol of daily fluconazole administration with additional administration of amphotericin administered subcutaneously has also been reported (Govendir et al., ; Kido et al., ; Woods & Blyde, ; Wynne et al., ). Black, Krockenberger, Kimble, & Govendir, demonstrated that oral fluconazole administration alone at 10 mg/kg twice daily is unlikely to be effective against C. gattii .…”
Section: Introductionmentioning
confidence: 99%